Analysis of Drug Management in the Pharmacy Installation of the Jiwa Tampan Hospital, Riau Province, 2022 - Siti Aisyah; Nopriadi Nopriadi; Budi Hartono; Mishbahuddin Mishbahuddin; Hetty Ismainar (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze drug management in the Pharmacy Installation of the Jiwa Tampan Hospital at Riau Province in 2022. The research method used is qualitative with a descriptive approach. The research location is carried out at the Jiwa Tampan Hospital at Riau Province, especially the Pharmacy Installation. The research time starts from a preliminary study conducted in January 2022 and then this research is carried out on 17 May to 04 July 2022. The selection of hospital in this study is carried out by purposive sampling method. The total of main hospital and supporting hospital are 14 hospitals. The data analysis technique that will be used by the researcher is a qualitative data analysis technique with content analysis. Based on the results of the study show that drug management in the Pharmacy Installation of the Jiwa Tampan Hospital at Riau Province in 2022 is running well, but there are several components that are not optimal.